Failure Investigation and Product Quality Optimization for Movable Fairing Aero Composite Part - Jamaluddin, Khairuddin (2018)
In every manufacturing based company, quality play a bigger role as the deliverable product must follow a specific requirement stating in the drawing or condition of supply. Any deviation of the product from the drawing or condition of supply would cause a nonconformance to the company that supplies the product. A case study performed in one local based aerospace company (company X), has focusing into product optimization and related quality control of Moveable Fairing composites part, that prone to experience the highest defect possibilities due to manufacturing processes. In order to eliminate the defect, the real root cause and corrective action were ascertained. Furthermore, data analyses also need to determine which defect that contribute the most to the overall quality performance. In company X, the target for quality performance of movable fairing composites part manufacturing is targeting into 20% reduction from previous year. However, there are too many variables which cause formation or presence of defects in movables fairing composites parts during real manufacturing operation. Manual monitoring using common job-sheet are too loose and not stringent. It was based only on the dimensional conformance without the usage of statistical or any quality tools. Hence, in this research the job of Quality Optimization for movable fairing composite part would be more effective to be applied. The Pareto Chart method was proposed as effective route to optimize the quality performance and solving the defects problems at their root cause. It was found that, through this research, by having the utilization of quality tools like Pareto Chart in monitoring the quality of movable fairing part, about 83% elimination of possible defects has been achieved. In the end, this research is beneficial in providing the real solution to the company X in boosting their profits.